Influence of caffeine on blood pressure and platelet aggregation - Cavalcante,José Wilson S. (2000)
OBJECTIVE: Studies have demonstrated that methylxanthines, such as caffeine, are A1 and A2 adenosine receptor antagonists found in the brain, heart, lungs, peripheral vessels, and platelets. Considering the high consumption of products with caffeine in their composition, in Brazil and throughout the rest of the world, the authors proposed to observe the effects of this substance on blood pressure and platelet aggregation. METHODS: Thirteen young adults, ranging from 21 to 27 years of age, participated in this study. Each individual took 750mg/day of caffeine (250mg tid), over a period of seven days. The effects on blood pressure were analyzed through the pressor test with handgrip, and platelet aggregation was analyzed using adenosine diphosphate, collagen, and adrenaline. RESULTS: Diastolic pressure showed a significant increase 24 hours after the first intake (p<0.05). This effect, however, disappeared in the subsequent days. The platelet aggregation tests did not reveal statistically significant alterations, at any time during the study. CONCLUSION: The data suggest that caffeine increases diastolic blood pressure at the beginning of caffeine intake. This hypertensive effect disappears with chronic use. The absence of alterations in platelet aggregation indicates the need for larger randomized studies.